Pengaruh Perencanaan Pajak, Pertumbuhan Penjualan, dan Good Corporate Governance Terhadap Nilai Perusahaan - Noviyanti Rahmah; Adhitya Putri Pratiwi (CV. ITTC INDONESIA, 2024)
This study aims to determine the influence of Tax Planning, Sales Growth, and Good Corporate Governance on Company Value. The population of this study is the Consumer Cylicals Sector listed on the Indonesia Stock Exchange (IDX) in 2018-2022. This research is a quantitative research with media in the form of financial statements and sample selection is carried out based on the purposive sampling method so as to produce 17 (seventeen) companies. The analysis technique used in this study is Panel Data Analysis. Data processing in this study uses the Eviews 10 software application, with the results of the study showing that the Effected of Tax Planning, Sales Growth, and Good Corporate Governance simultaneously affect Company Value. Tax planning had a positive effect on Company Value, Sales Growth had a negative effect on Company Value, Independent Board of Commissioners had a negative effect on Company Value, Institutional Ownership had a negative effect on Company Value.